Cognitive–communication disorders in children with traumatic brain injury. (6th October 2014) - Turkstra, Lyn S; Politis, Adam M; Forsyth, Rob
<x xml:space="preserve">Abstract</x> Children with moderate to severe traumatic brain injury (TBI) are at risk of developing cognitive–communication disorders that have devastating effects on their school life, family life, and social life. These problems can be difficult for families to describe and may be overlooked by community‐based providers who are unfamiliar with TBI sequelae. To support the identification and management of cognitive–communication disorders, we review the common signs and symptoms of these disorders in children with TBI and discuss principles of assessment and intervention.